USING STOCK ASSESSMENT TO INVESTIGATE THE SUSTAINABLE FISHERIES OF THE YELLOW MANDI Pimelodus maculatus IN THE UPPER URUGUAY RIVER, SOUTHERN BRAZIL - Gianfrancisco Schork; Samara Hermes-Silva; Renata Maria Guereschi; Evoy Zaniboni-Filho; Alex Pires de Oliveira NUÑER (Boletim do Instituto de Pesca)
The yellow mandi Pimelodus maculatus is a medium-sized species with a wide geographical distribution. The species is very common in the Neotropical region, representing an important share of fishing activity in several Brazilian reservoirs. Therefore, the objective of this study was to evaluate the current situation of the yellow mandi fish stock in the Itá reservoir, located in the Upper Uruguay River. Data collected from January 2004 to December 2016 were used to estimate growth, mortality, and fish recruitment rates. In addition, a stock assessment was performed, and the results were used to verify the status of the fishery. The mean of the population parameters were: total length (L) = 55.65 cm; length at which 50% of fish are vulnerable to capture (Lc) = 23.08 cm, growth rate (k) = 0.260 year-1, growth performance index (Ø) = 3.047, natural mortality rate (M) = 0.537, fishing mortality rate (F) = 0.413, total mortality rate (Z) = 0.95, exploitation rate (E) = 0.434, maximum age (Tmax) = 6.68 years. The growth curve obtained via ELEFAN I revealed that fishing operates on eight of the eleven cohorts of the population. Yellow mandi stock assessment did not show signs of fish overexploitation or any risk of depletion.